EXPERIENCE WITH e-LEARNING IN THE MATHEMATICS TEACHING - NAVRATIL, Miroslav; STARA, Ludmila (Trends in education, 2010)
The article describes using the e-Learning environment UIS Mendelu for creating electronic materials. It contains a short list of possibilities provided by this system and description of study material prepared for students of basic math courses. There are also mentioned some advantages and disadvantages of electronic study materials.
Keywords: e-Learning; mathematics; educational process; electronic study materials.